PRIORITIES FOR THE DEVELOPMENT OF STRATEGIC MANAGEMENT ACCOUNTING: DIGITAL ECOSYSTEM - Khodzytska, Valentyna (Current Problems of Sustainable Development, 2026)
Influenced by the exponential growth of data volumes and the development of digital technologies, the current stage of the development of the world economy, known as the Fourth Industrial Revolution, is marked by a radical transformation of the nature of economic relations. Digital transformation of business is based on an updated management process and the implementation of individual software products. Digital transformation is a complex strategic process that includes a fundamental transformation of business models, organizational structures and company culture in order to create new value using digital tools [7, 35, 50, 51]. According to a global survey of company executives, seventy percent of company executives believe that digital transformation is important for the survival of the world after the pandemic, and that in 2026 the priority will be focused on optimizing financial processes using blockchain and artificial intelligence [50]. Similarly, SolveXia research predicts that automation of finance will reduce operating costs by 30-50% by 2025, and FloQast claims that automation of financial reporting will increase efficiency by 40% [51, 52]. The current stage of development of the global and national economy is characterized by an unprecedented level of dynamism, uncertainty and the manifestation of systemic crises. In such conditions, traditional approaches to management accounting, focused on retrospective analysis of internal financial indicators, lose their effectiveness. To ensure the viability and competitiveness of enterprises, there is an objective need to develop strategic management accounting. which focuses on the external environment, risk forecasting, analysis of competitor behavior and creation of long-term valAt the same time, the rapid development of Industry 4.0 and 5.0 technologies (artificial intelligence, Big Data, cloud computing, blockchain) is radically changing the architecture of corporate governance. The single use of isolated software products no longer meets the needs of management. The task of forming a holistic digital ecosystem of the enterprise arises. Such an ecosystem allows integrating financial and non-financial data in real time (Real-Time Data), ensuring continuous information exchange between all structural divisions and external stakeholders.
Keywords: digitalization; strategic management accounting; risks; IFRS; relevance; digital ecosystem; strategic paradigm; block chain